Penerapan Model Guided Discovery Learning Dengan Mind Mapping Untuk Meningkatkan Kreativitas Mahasiswa - Putri, Alfiani Athma; Susanti, Reni Dwi; Dintarini, Mayang (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2017)
The aim of this research is to describe the application of guided discovery learning model with mind mapping that could increase students creativity in compiling the thesis proposal. The approach of this research is descriptive qualitative with the research subjects are 3rd-grade students of Mathematics study program of UMM that taking the Research Methodology course.            The steps of this research are planning, implementation, analysis, and evaluation respectively. The Guided discovery Model Learning with Mind Mapping is applied at the implementation stage, where students are required to develop research proposals based on guided discovery learning steps, that is (1) provision of stimuli, (2) problem identification, (3) completion data, (4) data processing, (5) verification, and (6) generalizations, which have been compiled in textbooks of Research Methodology courses. The results of this research found that students have difficulties in determining the topic of research, the reference, and the types of research and instruments to be used.Keywords: guided discovery learning, mind mapping, creativityKeywords: guided discovery learning, mind mapping, creativity